Fulminant Peritonitis Presumably Caused by Panton‐Valentine Leukocidin‐Positive Staphylococcus aureus in a Girl on Peritoneal Dialysis. Issue 4 (11th August 2013) - Battelino, Nina; Pokorn, Marko; Švent‐Kučina, Nataša; Križan‐Hergouth, Veronika; Novljan, Gregor
Abstract Peritonitis is a significant complication of peritoneal dialysis (PD) and the most common cause of technique failure. Panton‐Valentine leukocidin (PVL), a cytotoxin produced by certain strains of Staphylococcus aureus (SA), causes destruction of neutrophils, and is associated with severe invasive infections. We present a 2.5‐year‐old girl on PD, who presented suddenly with an unusually fulminant and protracted course of peritonitis. Only a few hours after the onset of clinical signs, septic shock developed. PVL‐positive methicillin‐sensitive SA (MSSA) was grown and initial empiric antibiotic treatment changed to flucloxacillin and rifampicin in order to minimize toxin production. In spite of adequate antibiotic treatment and PD‐catheter removal, recovery was slow. No PD‐related peritonitis in children associated with PVL‐producing strains have been reported so far and no specific recommendation exists for treatment. We speculate that PVL contributed to the severity and outcome of peritonitis in our patient.